2020
DOI: 10.1177/1747016120943622
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of COVID-19 tracking apps – challenges and voluntariness

Abstract: As COVID-19 continues to spread, a variety of COVID-19 tracking apps (CTAs) have been introduced to help contain the pandemic. Deployment of this technology poses serious challenges of effectiveness, technological problems and risks to privacy and equity. The ethical use of CTAs depends heavily on the protection of voluntariness. Voluntary use of CTAs implies not only the absence of a legal obligation to employ the app but also the absence of more subtle forms of coercion such as enforced exclusion from certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 13 publications
0
61
0
4
Order By: Relevance
“…As a matter of fact, our study is among the first scientifically based literature that addresses the antecedents of adoption of COVID-19 CTA. Thus, this study fills the void identified by previous studies [5,31] who called for scientific approach and empirical evidence to guide relevant authorities in the implementation of CTA. Second, as destinations begin to ease the lockdown, different authorities ponder key strategies to reset destination attractiveness and engender safety of tourists [2].…”
Section: Theoretical Implicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…As a matter of fact, our study is among the first scientifically based literature that addresses the antecedents of adoption of COVID-19 CTA. Thus, this study fills the void identified by previous studies [5,31] who called for scientific approach and empirical evidence to guide relevant authorities in the implementation of CTA. Second, as destinations begin to ease the lockdown, different authorities ponder key strategies to reset destination attractiveness and engender safety of tourists [2].…”
Section: Theoretical Implicationsmentioning
confidence: 85%
“…Additionally, in the midst of the stiff resistance to CTA adoption, users' concerns that have resonated across countries and destinations is the assurance of the protection of their privacy [32]. To the best of our knowledge, there is no study that has yet examined the role of structural assurance on users' trust and their intention to use the CTA, even as previous studies [5,31] have highlighted the critical place of an empirical evidence to guide relevant authorities.…”
Section: Introductionmentioning
confidence: 99%
“…The New Zealand COVID TRACER app thus relies upon high levels of trust (and enthusiasm) for people to download and utilise it. Evidence suggests that such a reliance makes such apps vulnerable to increased anxiety levels within a population (Klar and Lanzerath 2020). However, even when such trust exists, an opt-in system also creates a number of practical challenges.…”
Section: Taiwan's Covid Responsementioning
confidence: 99%
“…But they can also be more fundamental, where ethically well-justified positions come into conflict and resolutions of such conflicts are not obvious and straightforward. An example might be the controversy over mobile tracking and tracing apps during the COVID-19 crisis, in which competing demands from privacy campaigners and public health experts have led to a number of controversies over how such technologies could and should be used to limit the spread of the disease (Klar and Lanzerath 2020). This is also a good example of the problems in drawing a boundary around a socio-technical innovation ecosystem in terms of jurisdictions, data, technical platform etc.…”
Section: Determining Flourishingmentioning
confidence: 99%